Proteases in cellular slime mold development: evidence for their involvement. - Fong, D (1979)
Protein degradation appears to be essential for normal differentiation in the cellular slime mold Dictyostelium discoideum. Several protease inhibitors block normal differentiation, and in most cases this inhibition can be reversed by addition of amino acids. For example, chloroquine, which inhibits slime mold cathepsin B activity, interferred with development by blocking sorocarp formation, and this inhibition was reversed by the addition of amino acids. Tosyllysyl chloromethyl ketone also blocked development, and this inhibition was reversed by simultaneous additions of amino acids and glutathione. Moreover, the addition of antipain and leupeptin delayed sorocarp formation. These results, together with the finding reported earlier that cathepsin B activity is differentially localized in the prestalk-prespore zones of the migrating slugs, suggest that proteolysis might play a regulatory role in cellular slime mold differentiation.